Coccygectomy for chronic refractory coccygodynia in pediatric and adolescent patients - Hisham Almohamady Almetaher; Mohamed Awad Mansour; Mohamed Ali Shehata (Wolters Kluwer Medknow Publications, 2021)
Aims: Coccygodynia (also known as coccydynia and coccyalgia) described for the first time by Simpson in 1859. It is a disabling pain in the coccyx usually provoked by sitting or changing position from a sitting to a standing position. Treatment started with adjustment of ergonomics as specialized cushion for sitting, application of local heat, and oral analgesics. The aim of this study was to assess the results of total or partial coccygectomy for patients suffering from chronic refractory coccygodynia and not improving on conservative treatment in pediatrics and adolescents. Methods: The study included 22 patients, 8 of them with chronic refractory coccygodynia not responding to conservative management underwent partial or total coccygectomy using Key's surgical exposure after good preoperative preparation. Results: This study included 5 females (62.5%) and 3 males (37.5%), their ages ranged from 7 to 15 years. The results were excellent in 75% of patients and good in the remaining cases. The mean length of hospital stay was 1.43 ± 0.98 days. No significant intraoperative or postoperative complications were reported. The parents were satisfied in almost all cases in the long term follow up. Conclusions: Coccygodynia is a disabling problem, especially in pediatric patients. Coccygectomy is a feasible management option and has a favorable outcome when performed for an appropriate indication.